DINAMIKA MAKROEKONOMI INDONESIA, ANALISIS FAKTOR-FAKTOR PENENTU PERTUMBUHAN EKONOMI - Gunardi; Gunardi, Gunardi; Veranita, Mira; Turyandi, Itto; Wahyudi, Wahyudi; Kesumah, Priatna; Hutahaean, Limbert; Framesthi, Dyah Bayu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
This research aims to analyze the determinants of Indonesia's economic growth using a qualitative approach. By understanding the complex relationships among macroeconomic variables, it is expected to provide more effective policy recommendations to promote sustainable economic growth. The analysis results indicate that monetary policy, investment, and labor market conditions play crucial roles in determining the direction of economic growth. A stable monetary policy contributes to increased purchasing power and domestic consumption. Additionally, foreign direct investment (FDI) serves as a primary driver of growth by enhancing infrastructure and technology. Despite challenges such as global uncertainty and commodity price fluctuations, opportunities for growth remain wide open through innovation and the adoption of new technologies